Uso do direito político nas propagandas eleitorais com promessas de campanha cômica ou impossível - Oliveira, André Luiz Leite de (Universidade Federal Rural do Semi-Árido, 2017)
In a period of political effervescence, it is urgent to discuss the best ways of promoting the electoral debate by presenting ideas and political proposals capable of fostering the construction of social welfare and the solidification of the Democratic Rule of Law. However, the period before the vote has become a circus ring, since several candidates occupy the space of electoral propaganda to ridicule the suit, using merely comic (humorous) devices, unaccompanied by ideological or political bias, As well as many other voters who express themselves with apparently absurd electoral promises, such as ex-councilman Miguel Mossoró, who would build a bridge linking Natal-RN to Fernando de Noronha-PE, a distance of over 320 km ). These conducts translate into prejudice to the smoothness and dignity of the electoral process, under the pretext of freedom of communication. In this sense, it is mentioned the levers proposed by TCHAKHOTINE / MILLER, commonly used as mechanisms of acceptance of the interlocutor towards the candidate, creating favorable "mental states". This theory applies to the hypotheses presented in the present study, according to the research carried out, whose results demonstrated the impact on the voters 'memory, the candidates' performance through humor and the presentation of clearly unpromising promises. On this, art. 242 of the Electoral Code is prohibited by the creation of mere "mental states" artificially created in public opinion. Regarding this, the judiciary has been manifesting preferring the prevalence of freedom of expression, despite the express legal prohibition and the clear violation of the dignity and smoothness of the electoral process, in addition to the principle of veracity, the basis of electoral propaganda. Finally, jurisprudential innovation is encouraged, so that the judicial control acts to stop such advertisements because they are mere psychic artifices, without prejudice to legal sanctions.
Artigo Acadêmico
Keywords: Propaganda eleitoral. . . . . . , .; Artifícios cômicos; Promessas impossíveis; Liberdade de comunicação; Dignidade do pleito eleitoral; Lisura; Artigo 242; Código eleitoral; CIENCIAS SOCIAIS APLICADAS::DIREITO